A retrospective study to assess the efficacy, safety, and drug survival of secukinumab in plaque psoriasis patients in China. Issue 5 (12th August 2021) - Wang, Yu; Wang, Xiaohua; Yu, Yixin; Yuan, Liyan; Yu, Xiaoling; Yang, Bin
Abstract: Secukinumab, a full human immunoglobulin G1κ monoclonal antibody that targets interleukin‐17A, has demonstrated remarkable efficacy and appreciable tolerance in patients with moderate‐to‐severe psoriasis. However, data on its real‐life performance, particularly on drug survival in China are limited. To investigate the efficacy, safety, and drug survival of secukinumab in Chinese patients with psoriasis, we conducted a monocentric retrospective study of 66 patients with moderate‐to‐severe psoriasis to followed‐up for 52 weeks. At week 12, 86.4%, 57.6%, and 10.6% of the patients attained 75% improvement in psoriasis area and severity Index (PASI) score from baseline (PASI 75), PASI 90, and PASI 100 responses, respectively. The quality of life of patients markedly improved. The overall survival rate was 74.2%. Adverse events occurred in 30 patients (45.5%). The results revealed favorable efficacy, safety, and tolerability of secukinumab in the treatment of patients with psoriasis and provided data on drug survival in real‐life clinical setting in China for the first time.